Immobilization of gelatin onto poly(glycidyl methacrylate)-grafted polycaprolactone substrates for improved cell-material interactions - Yuan, Shaojun (2013)
To enhance the cytocompatibility of polycaprolactone (PCL), cell-adhesive gelatin is covalently immobilized onto the PCL film surface via two surfacemodified approaches: a conventional chemical immobilization process and a surface-initiated atom transfer radical polymerization (ATRP) process. Kinetics studies reveal that the polymer chain growth from the PCL film using the ATRP process is formed in a controlled manner, and that the amount of immobilized gelatin increases with an increasing concentration of epoxide groups on the grafted P(GMA) brushes. In vitro cell adhesion and proliferation studies demonstrate that cell affinity and growth are significantly improved by the immobilization of gelatin on PCL film surfaces, and that this improvement is positively correlated to the amount of covalently immobilized gelatin. With the versatility of the ATRP process and tunable grafting efficacy of gelatin, this study offers a suitable methodology for the functionalization of biodegradable polyesters scaffolds to improve cell–material interactions.